2022
DOI: 10.3803/enm.2022.1402
|View full text |Cite
|
Sign up to set email alerts
|

Development of Metabolic Synthetic Lethality and Its Implications for Thyroid Cancer

Abstract: Cancer therapies targeting genetic alterations are a topic of great interest in the field of thyroid cancer, which frequently harbors mutations in the RAS, RAF, and RET genes. Unfortunately, U.S. Food and Drug Administration-approved BRAF inhibitors have relatively low therapeutic efficacy against BRAF-mutant thyroid cancer; in addition, the cancer often acquires drug resistance, which prevents effective treatment. Recent advances in genomics and transcriptomics are leading to a more complete picture of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Cancer cells exhibit metabolic reprogramming that supports their heightened energetic and biosynthetic demands. Thyroid cancer represents one of the most common endocrine malignancies, characterized by abnormal growth and proliferation of thyroid follicular cells [38]. Over the past decades, substantial progress has been made in elucidating the metabolic alterations that underlie the development and progression of thyroid cancer [39][40][41].…”
Section: Metabolism In Thyroid and Other Cancersmentioning
confidence: 99%
“…Cancer cells exhibit metabolic reprogramming that supports their heightened energetic and biosynthetic demands. Thyroid cancer represents one of the most common endocrine malignancies, characterized by abnormal growth and proliferation of thyroid follicular cells [38]. Over the past decades, substantial progress has been made in elucidating the metabolic alterations that underlie the development and progression of thyroid cancer [39][40][41].…”
Section: Metabolism In Thyroid and Other Cancersmentioning
confidence: 99%
“…1) Accumu-lating evidence has shown that cellular energy metabolism in remodeled tumors affects tumor behavior, which determines treatment sensitivity. 2,3) Although thyroid cancers harbor genetic mutations that may provide the underlying cause of metabolic heterogeneity 4,5) and altered cellular energy metabolism, the clinical significance of altered cellular energy metabolism remains to be explored.…”
Section: Introductionmentioning
confidence: 99%